Leveraging Religious Capital: Teacher Agency and Curriculum Reform in Indonesian Islamic Schools - Amalia, Eka Rizki (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Curriculum transformation in Indonesian Islamic educational institutions (madrasahs) is essential in addressing globalization challenges and technology development. This research investigates the intersection of religious capital and teacher agency in these institutions, with the objective of understanding how Islamic values can shape curricular innovation without abandoning core Islamic educational principles. Systematic library-based research was employed to select the literature published in peer-reviewed publications from 2015 to the present using the following databases: Scopus, ERIC, IEEE Xplore, Web of Science, Google Scholar, JSTOR, ProQuest and ScienceDirect with the keywords listed to be included were, "curriculum reform," "Islamic schools," "religious capital," and "teacher agency." The results show how teachers draw on religious capital—expertise of religious text, the practice of religion, and community networks—to articulate curriculum changes in ways centering on Islamic values. The study highlights how religious capital can both enable teachers and constrain innovations. The findings offer practical implications: Policymakers must recognize religious capital's nuanced role in curriculum reform, ensuring that educational institutions meet pedagogical needs not at the expense of religious education's integrity. This interaction in the context of a wider Islamic educational setting should be unpacked in future research in order to extrapolate implications for sustainable and inclusive educational policies.